Plan de negocios para el diseño de un centro de recreación familiar en la ciudad de Quevedo, para el año 2012 - Hernández Soria, Angélica María (2012)
The overall objective for this research arose was: Run organizing a business plan, starting from an adequate market research generate business opportunities for the design of a recreation and entertainment center, allowing recreation and social bonding, empowering mental and physical health, as well as generating tourism in the city of Quevedo, from the year 2012,deriving their main specific objectives, to establish market research to generate business opportunities for the creation and execution of business-related recreation, leisure and tourism in the city of Quevedo and surrounding areas.Within this context set out to answer the following research question: Is it feasible to organize a business plan, starting from an adequate market research to generate business opportunities for the creation of a center of recreation and entertainment, enabling the spread and social bonding, empowering mental and physical health, as well as generating tourism in the city of Quevedo, from the year 2012? In this way and by hypothesis was evident if adequate market research related to the activity of a family recreation center in the city of Quevedo, from the year 2012. It should be noted that the research was based on a descriptive and applied research aimed at studying, analyzing, describing and if necessary change the reality of the present nature of the problem under study Further research was supported by the use of techniques such as interviews and survey where information is sought and provided directly to draw the conclusions that there is a potential demand in the market it was directed to the business plan, which is formed households comprised on average of 4 people, they do not know a place that provides recreational services and have to leave town for family recreation activities, and that the report gives a technical and financial proposal according to the study financially and economically done we calculated values in the NPV = $ 280,042; IRR 48.37% are considered amounts to justify the performance and feasibility of this project, which will serve the residents of Canton Quevedo and furnish positively progress partner -economic thereof.